The unity of the capitalist economy and state : a systematic-dialectical exposition of the capitalist system - Reuten, G. A. (Historical materialism book series,, 2019)
In The unity of the capitalist economy and state, Geert Reuten offers a systematic exposition of the capitalist system, showing that the capitalist economy and the capitalist state constitute a unity. In its critique of contemporary economics, the book argues that in order to comprehend the capitalist system, one requires a full synthetic exposition of the economic and state institutions and processes necessary for its continued existence. A synthetic approach also reveals a range of components that are often obscured by partial analyses. In its systematic character, Reuten's work takes inspiration from Marx's provisional outline of the capitalist system in Capital, while also addressing fields that Marx left unfinished - such as the capitalist state.